2013
DOI: 10.4028/www.scientific.net/amr.747.623
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mold Temperature and Casting Temperature on Hot Cracking in Al-4.5 wt.% Cu Alloy

Abstract: Hot cracking is an important defect that occurs during solidification of aluminum-copper alloys. In this present work, the effects of mold temperature and casting temperature on hot cracking in the Al-4.5 wt.% Cu alloy has been studied using a ring mold for hot cracking assessment. For the experimental conditions, three mold temperatures between 150 and 350°C and three casting temperatures between 670 and 770°C were studied and Al-7 wt.% Si alloy was used as reference for comparison. The results showed Al-7 wt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Meanwhile, the temperature of 737°C (superheat temperature of 124°C) was provided to the Al-7wt.%Si alloy. The results showed that hot tearing significantly reduced with decreasing pouring temperature [21]. Another previous study also showed that the effect of three different pouring temperatures (700, 750, and 800°C) was predicted for A356 and M206 alloys on hot tearing susceptibility.…”
Section: Parameter Of Pouring Temperaturementioning
confidence: 66%
See 2 more Smart Citations
“…Meanwhile, the temperature of 737°C (superheat temperature of 124°C) was provided to the Al-7wt.%Si alloy. The results showed that hot tearing significantly reduced with decreasing pouring temperature [21]. Another previous study also showed that the effect of three different pouring temperatures (700, 750, and 800°C) was predicted for A356 and M206 alloys on hot tearing susceptibility.…”
Section: Parameter Of Pouring Temperaturementioning
confidence: 66%
“…( 21). (21) This indicated that a crack was formed when the HCS was greater than one, showing that the model was used to qualitatively and quantitatively predict hot tearing. In this calculation, εθθ was obtained from the FEM simulation, with εfr being 0,0018 [96].…”
Section: Hot Tearing Criteriamentioning
confidence: 95%
See 1 more Smart Citation